2002
DOI: 10.1051/0004-6361:20020574
|View full text |Cite
|
Sign up to set email alerts
|

Time variation of SWS spectra of M-type Mira variables

Abstract: Abstract. The M-type Mira variable star, Z Cyg, was observed with the Short-Wavelength Spectrometer (SWS) on board the Infrared Space Observatory (ISO) 7 times at roughly 60 day intervals over one and a half period. The infrared spectrum (2.38-45.2 µm) of Z Cyg shows prominent silicate emission bands at 10 µm and 18 µm and displays quite large variations over the observed period. The variation in the infrared spectrum of Z Cyg is synchronized with the visual light curve. The circumstellar emission and the 10 µ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 50 publications
(76 reference statements)
1
15
0
Order By: Relevance
“…Vandenbussche et al (2002) and Onaka et al (2002) presented several spectra of stellar sources processed from OLP 10 pipeline results. To increase the sample of spectra for comparison, we also examine results from earlier versions of the pipeline from other authors.…”
Section: Comparison With Other Processing Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Vandenbussche et al (2002) and Onaka et al (2002) presented several spectra of stellar sources processed from OLP 10 pipeline results. To increase the sample of spectra for comparison, we also examine results from earlier versions of the pipeline from other authors.…”
Section: Comparison With Other Processing Methodsmentioning
confidence: 99%
“…On the other hand, our spectra are considerably less noisy from 3.0 to 3.7 lm, probably because we discard most of the out-of-band data from Bands 1D and 1E and they do not. Onaka et al (2002) observed Z Cyg, an oxygen-rich M5 star, as part of a study of infrared variability in circumstellar dust emission. Figure 10 compares our spectra with the same observations reduced by Onaka et al (2002) from OLP 10.1 pipeline output.…”
Section: Comparison With Other Processing Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Much of this work is based on multi-wavelength studies of various components or regions in these atmospheres including masers and radio photospheres (Reid & Menten, 1997Cotton et al 2008), molecular photospheres, especially with optical/infrared interferometry (Ragland et al 2008, Perrin et al 2004, and dust production, especially with respect to pulsational phase (Onaka et al 2002, Matsuura et al 2002, Marengo et al 2007). This study seeks to increase our information on the interaction between pulsation and dust production by obtaining simultaneous data from space (infrared spectroscopy) and the ground (infrared interferometry) on a chemically complete sample of mira variables.…”
Section: Introductionmentioning
confidence: 99%
“…Just to mention a few, H 2 O, SiO, CO 2 , CO and silicate dust features have been detected in stars with atmospheric C/O ratio < 1, while C 2 H 2 , HCN, CS, C 3 and carbonaceous dust (SiC and amorphous carbon) have been found in carbon stars, having C/O > 1. The presence and strength of these spectral features depends on the chemistry of the stellar atmosphere [5,6] and the mass loss rate, and can change with time [7] because AGB stars are Long Period Variables generically classified as Mira, semiregular or irregular pulsators.…”
Section: Introductionmentioning
confidence: 99%